Pengaruh Ekonomi Pasar pada Teknologi Pertanian di Minahasa - Lefrand W. Sondakh; D. Sembel (Antropologi Indonesia, 1995)
The people of Minahasa appeared to have always been responsive to market signals. Geertz's view of a dynamic expansion of the economy in outer island of Indonesian seems applicable to Minahasa. The Minahasan people appear to have shifted rapidly from one crop to another, from one agricultural technology to another and the change can be explaine by the change of factors prices. The influence of market economy seems to have affected mapalus, which is a traditional means to achieve social integration that seems to have been gradually and rapidly disappearing. It still possesses the name and the value, but has not longer been a common phenomenon of social integration to tackle various economic activities and problems. Most benefits previously provided through mapalus appear to have become available at cheaper process through the market. Very recently, an attempt to revive mapalus as a form of not only social but also economic integration has been made. It however remains an open question whether such attempts would be successful.